2017
DOI: 10.1007/s00468-017-1559-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimum wood density of conifers portrays changes in early season precipitation at dry and cold Eurasian regions

Abstract: SummaryIn conifers tracheids fulfill most of the main wood functions (mechanical support, water transport). Earlywood tracheids account for most hydraulic conductivity within the annual tree ring. Therefore, dry conditions during the early growing season, when earlywood is formed, should lead to the formation of narrow tracheid lumens and a dense earlywood. Here we test if there is an inverse relationship between minimum wood density and early growing-season (spring) precipitation. We study growth and density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 60 publications
5
33
0
Order By: Relevance
“…Moreover, in addition to cambial age and growth rates of tree-ring width, the annual variations in wood density can be partially explained by climatic conditions [24]. For instance, Camarero et al [14] found a significant relationship between the minimum density and spring precipitation in P. nigra and P. sylvestris.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, in addition to cambial age and growth rates of tree-ring width, the annual variations in wood density can be partially explained by climatic conditions [24]. For instance, Camarero et al [14] found a significant relationship between the minimum density and spring precipitation in P. nigra and P. sylvestris.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, assessing the effect of pruning on wood density, taking into consideration pruning characteristics (e.g., pruning height, crown ratio, branch and knotty core sizes) should also form part of any further research work [21,59]. Finally, under the current context of global change, studying the effects of climate on wood properties in different species would be particularly pertinent [14,24].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of drought effects over low temperature restrictions on growth suggests that warming-induced water limitation will progressively spread over areas of North Asia-having low precipitation but, also, very low temperatures (i.e., under extreme continentality)-as already observed in Yakutia [56]. Drought effects on Scots pine may not be limited to growth impairment, but they may also hamper the formation of a functional xylem structure via a reduction of cell lumen and wall thickness, as shown for the region [33,63].…”
Section: Drought Rather Than Low Temperatures Determines Long-term Rementioning
confidence: 98%
“…The cell dimensions that drive earlywood density variation are also controlled by growing season temperature, but because variations in deposited cell wall material is secondary to earlywood cell enlargement variations, high temperatures mainly mean larger cells and thus lower density (Björklund et al, ). Likewise, in drought prone environments, dry years appear to have a negative effect on earlywood cell enlargement and to yield high density (Camarero et al, ; Camarero et al, ). Latewood density appears to modestly increase in wet years (Cleaveland, ), most likely due to increased deposition in the cell wall, but this has not been explicitly studied.…”
Section: Current Understanding Of Wood Density In Tree Ringsmentioning
confidence: 99%